Properties of butt joint from acacia mangium, shorea spp and Vatica spp / Wan Mohd Hafeizullah Wan Yusoff - Wan Yusoff, Wan Mohd Hafeizullah (2007)
Butt joint is a sample joint use in furniture production and constructions. The purpose for this study is to know the properties of butt joint from the three types of wood species, such as Acacia mangium, Shorea spp and Vatica spp. The properties of butt joint will test with bending testing using British standard. Raw material is come from the wood waste at the workshop. The factor of glue, moisture content, and clamping process will not effect to the properties of butt joint because its follow the step. The different of raw material is a main factor why its produce and to determine which one of the woods is suitable for butt joint making.